Comparison of surgical duration of canine ovariectomy and ovariohysterectomy in a veterinary teaching hospital. (28th October 2013) - Harris, K. P.; Adams, V. J.; Fordyce, P.; Ladlow, J.
Abstract: Objective: To prospectively evaluate ovariectomy and ovariohysterectomy via midline coeliotomy when being employed by supervised final year veterinary students for the purpose of routine canine neutering. Methods: One hundred and eight female dogs of various breeds, presented to a veterinary teaching hospital for neutering, were randomly allocated to one of two surgery groups, ovariectomy or ovariohysterectomy. The specified procedure was performed by a supervised final year veterinary student. If the duration of surgery exceeded 2 hours or if major surgical or anaesthetic complications occurred, the supervising surgeon intervened to complete the procedure. Results: Data analysed included age, weight, time from first incision to start of closure, duration of closure, total surgical time and length of incision. Fifty‐four dogs underwent each procedure. There was no significant difference between the two surgery groups for any of the measured variables. Clinical Significance: Ovariectomy is not associated with shorter surgical times or smaller abdominal incisions than ovariohysterectomy when employed by inexperienced surgeons. As no major complications novel to ovariectomy occurred in this cohort of dogs, this study adds support to the existing literature indicating that ovariectomy is an acceptable alternative to ovariohysterectomy for canine neutering.